Spontaneous bacterial peritonitis: A rare manifestation of expanded dengue syndrome - Jaspreet Kaur; Jasmine Singh; Yuvraj Singh Cheema (Turkish Journal of Emergency Medicine)
Abdominal pain is a usual presentation in dengue virus infection. The commonly reported causes of abdominal pain in dengue fever are pancreatitis, peptic ulcer disease, hepatitis, and acalculous cholecystitis. Spontaneous bacterial peritonitis (SBP) is a very unusual and rarely reported cause. The etiology of the acute abdomen along with nonresolving fever in dengue infection should be carefully diagnosed and managed accordingly. We report the case of a young female with no previous comorbidities who presented with complaints of fever and abdominal pain. On detailed investigations, she was diagnosed suffering from SBP, a rare type of expanded dengue syndrome.